2008
DOI: 10.1145/1314215.1314229
|View full text |Cite
|
Sign up to set email alerts
|

Women and men in the IT profession

Abstract: Fewer women work in or achieve the same job levels as men in corporate America today. In the IT profession, recent estimates (2006) suggest that women make up only 26% of IT professionals in the U.S. where they're outnumbered by men six to one in leadership positions [3,6]. What explains these lower levels of professional achievement for women in IT? Unfortunately, few facts are available to inform the answer, though numerous suppositions have been offered, including that women have less innate ability or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…McKinney et al [11] regards the growing demand of IS professionals on the job market as an "input problem" for IT-Firms. According to this statement, the overwhelmingly part of the IS literature in the context of IS in education also focus on the question how to fill the pipeline of IS students.…”
Section: Research Backgroundmentioning
confidence: 99%
“…McKinney et al [11] regards the growing demand of IS professionals on the job market as an "input problem" for IT-Firms. According to this statement, the overwhelmingly part of the IS literature in the context of IS in education also focus on the question how to fill the pipeline of IS students.…”
Section: Research Backgroundmentioning
confidence: 99%
“…In the IT research, McKinney, Wilson, Brooks, O'Leary-Kelly, and Hardgrave (2008) report that in comparison to men, the surveyed women in IT reported many common motivators for entering the profession and more often indicated that job security, ease of entry, and flexible work hours were the primary reasons for entering the occupation. Prior research has specifically recognized some facets of job satisfaction (e.g., opportunity for advancement, job security, gratifying work, and compensation) as potential motivators for entry into the IT profession (McKinney, et al, 2008). Moreover, Davis and Kuhn (2003) found that many of these same facets (e.g., salary and nature of work) were important factors for IT workers leaving a job.…”
Section: Facets Of Job Satisfactionmentioning
confidence: 99%
“…A recent study has presented evidence that the under-representation problem is more of a supply/input problem than a retention/throughput problem -women are not entering technology-related careers in high numbers (McKinney, et al, 2008). This suggests that if we are to increase the number of women in IT, we need to focus attention to those who are making initial and transitional career choices, perhaps more than problems with differential turnover.…”
Section: Future Work In Under-representation and Job Choicementioning
confidence: 99%
“…Men may feel the need to learn the use of various ITEs because technologies are widely used by men, while women may feel less interested because IT use is considered as a male-dominated¯eld. In further exploring how women feel about IT adoption, McKinney et al (2008) observed that fewer women are present in the IT work force because IT-related work is considered as a male-dominated¯eld. This misconception may intimidate women and dissuade them from entering the IT workforce because they may be viewed as less competent.…”
Section: Gendermentioning
confidence: 99%